DIDACTIC FOUNDATIONS OF THE METHODOLOGY OF TEACHING SPECIALIZED SUBJECTS IN HIGHER EDUCATION: GOALS AND OBJECTIVES (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
This article provides a scientific and theoretical analysis of the didactic foundations, goals, and objectives of the methodology of teaching specialized subjects in the higher education system. The study examines the role of didactic principles, teaching methods, and educational tools in enhancing the effectiveness of specialized disciplines. Based on surveys, pedagogical observation, and analytical methods, the necessity of modernizing the teaching and learning process is substantiated. The results show that interactive and modern teaching methods are more effective in developing professional competencies compared to traditional approaches